The Effect Of Bumdes Governance On Village Economic Independence: A Case Study Of Bumdes Dadirejo In Bandungrejo Village - Devi Ratna Sari; Nur Siyami; Rusmiyatun Rusmiyatun (International Journal of Economics, Commerce, and Management, 2025)
This study aims to explore the impact of Village-Owned Enterprise (BUMDes) governance on village economic independence, with a case study in BUMDes Dadirejo, Bandungrejo Village, Bayan District, Purworejo Regency. The focus of this study is to determine the extent to which good governance principles can encourage increased village economic independence, particularly in terms of increasing Locally-Owned Income (PADes) and empowering village communities. This study uses a quantitative descriptive-verification approach, involving 60 respondents consisting of village officials, BUMDes managers, and community representatives. Data collected through questionnaires, interviews, and documentation were analyzed using validity, reliability, correlation, and regression tests using SPSS. The results show that good BUMDes governance has a positive and significant influence on village economic independence. The application of the principles of transparency, accountability, participation, responsibility, and institutional independence in BUMDes contributes to increasing local economic capacity and community participation in village development. These findings confirm that BUMDes management based on the principles of good governance can be a major catalyst in achieving sustainable rural development and improving the welfare of village communities.